PATTEREN OF CHEST INJURIES DURING ROAD TRAFFIC ACCIDENT IN PATIENTS PRESENTED TO EMERGENCY DEPARTMENT OF AIMS MUZAFFRABAD - Kayani, Ziyad Afzal; Gilani, Irum; Manzoor, Shagufta; Awan, Sarmud Lateef; Naqvi, Syed Zakir; Qureshi, Shagufta Sabir (Pakistan Journal of Physiology, 2021)
Background: Road traffic accident injuries are an important cause of mortality and morbidity. It is the major public health problem in every country across the world and causing approximately 5.8 million deaths per year. The Chest trauma is a disease that has worsened long with growing urbanization and industrialization; due to worldwide increases in violence, constructions and vehicle number. Methods: This study was conducted at Abbas Institute of Medical Sciences (AIMS) Muzaffarabad AJ&K from August 2020 to December 2020. The study was approved by Ethical committee of AIMS hospital. Convenient sampling technique was used. Hospital based retrospective descriptive cross-sectional study designs was used to assess patterns and outcomes of chest injuries among patients based on pre designed questionnaire presented to AIMS Muzaffarabad. The collected data were entered to SPSS, version 25 for analyses. Result: Most affected age group was young adults (63%) between 18yr-35yr.Nearly three fourth 72% of chest trauma patients were male and 28% were females. Majority of chest trauma patient arrived to health care facilities within 1 to 2 hours of trauma. Rib fracture was the commonest types of chest injury (39%) followed by hemopneumothorax (25%) and pulmonary contusion (7%). With regard to associated body region injured, extremities were the commonest region (47%). Conclusion: Chest injuries due to RTA predominantly affect the male and economically productive age group with high morbidity and mortality in this environment.